Sociolinguistics: Language variation and change analysis in the lyric song of Billie Eilish “Birds of a Feathers” - Rahel Purba; Rotua Pakpahan; Riby Siboro; Netania Saragih; Tiarma Intan Marpaung (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to find the comprehension of language variation and change in the industry of music in the present time. This research focuses on how lyrics in the current situation have been varied in order and evolve overtime. This research qualitative descriptive method, specifically in the new resources to finding song in the present time changing and differ across social culture. This study explores language variation and changes within the contemporary music industry by conducting a qualitative descriptive analysis of the lyrics of Billie Eilish’s 2024 single "Birds of a Feather." Focusing on phonological, lexical, morphosyntactic, and pragmatic features, this research examines how language in popular music evolves over time and reflects shifting social and cultural dynamics. The study illuminates how Eilish’s linguistic choices mirror broader sociolinguistic trends among Generation Z, emphasizing informal, conversational speech patterns, colloquial vocabulary, and innovative syntactic structures influenced by digital communication and social media. Through line-by-line analysis, the research reveals how these linguistic features construct authenticity, intimacy, and group identity, positioning the song as a dynamic site of language variation and sociocultural meaning. This work contributes to filling gaps in sociolinguistic research on mainstream English-language pop music and highlights the significant role of youth-driven language practices in shaping contemporary popular culture.